Sistem Layanan Pengaduan IT Berbasis Website Di SMK Bhina Tunas Bhakti - Dwimas Ananda; Endang Supriyati; Tri Listyorini (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The Bhina ​​Tunas Bhakti Juwana Vocational School IT team is a unit team at Bhina ​​Tunas Bhakti Juwana Vocational School which has the task of managing media and everything related to IT. With current reporting techniques, reporting problems is still relatively slow and has an impact on the IT team's slow resolution of complaints from units or rooms experiencing problems. Therefore, the author has the initiative to build an IT Complaint Service System at Bhina ​​Tunas Bhakti Juwana Vocational School. This system is designed to provide reporting, monitoring and IT problem solving services in the school environment. The research methodology used is a qualitative method that uses observation, interview and literature study techniques in data collection. In designing the system, it refers to an object-oriented approach, so UML (Unified Modeling Language) is used. The output of this research will be a website-based IT complaint service system implemented at Bhina ​​Tunas Bhakti Juwana Vocational School.